Local Versus Oversea Media: Pro’s and Con’s Views on the Practice of Political Dynasty in the 2024 Presidential Election - Nauvallina, Fauzia Hasna; Khristianto, Khristianto (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
In order to know the difference between the local and overseas media in delivering the news and elaborating on the “political dynasty” topic, the researcher conducted research on Najwa Sihab YouTube channel titled “Butet Kartaredjasa dan Petinggi PROJO Bicara Putusan MK” as the local media, and South China Morning Post titled “Nepotism May Win Indonesia’s 2024 Election”. There are two theories that were used to analyze the data, attitude aspects of appraisal theory (Martin & White, 2005), as well as the ideological square from (van Dijk, 2006). In addition, in the process of collecting the data for the analysis process, the researcher uses the qualitative descriptive approach (Miles & Huberman, 1994). The findings show that in local media there are two camps. Pro-Jokowi’s frequently used social esteem and de-emphasize negative things about us to deny negative accusation towards them. Contra-Jokowi’s mostly used social sanction and emphasize negative things about them to present the power abuse by the Jokowi’s party. In overseas media, there are only neutral party that frequently used social esteem and emphasizing negative things about them.